Morphological and molecular characterization of Geocenamus persici n. sp. (Nematoda: Merliniinae) from China - Zhang, Chenying; Munawar, Maria; Castillo, Pablo; Han, Shaojie; Zheng, Jingwu (Zootaxa, 2022)
A new stunt nematode species, Geocenamus persici n. sp. was recovered from the rhizosphere of peach (Prunus persica) in Zhejiang Province, China. This species is characterized by a dome-shaped labial region with six bulging sectors. The lip region is slightly offset from the rest of the body with five annuli; cuticle with over 30 longitudinal striae; stylet slender, 19 to 21 μm long; excretory pore at the anterior region of the basal pharyngeal bulb; tail cylindrical, 55 to 79 μm long with striated terminus. Males are common. Morphologically, the species is close to G. brevicaudatus, G. chengi, G. conicaudatus, G. quadrifer, G. rugosus, and G. tartuensis. Phylogenetic relationships of the new species placed G. persici n. sp. with other species of subfamily Merliniinae. However, it has a sister relationship with G. chengi. Since the new species is found in the peach plantations, our study will lay a foundation to initiate investigations on the occurrence of stunt nematodes in peach growing areas and will aid the researchers to determine whether this group of nematodes cause peach plantation diseases.